Nausea and vomiting in a colorectal ERAS program: Impact on nutritional recovery and the length of hospital stay. (December 2019) - Mc Loughlin, S.; Terrasa, S.A.; Ljungqvist, O.; Sanchez, G.; Garcia Fornari, G.; Alvarez, A.O.
Summary: Background & aims: Postoperative nausea and vomiting (PONV) and its impact on the hospital length of stay (LOS), have been extensively studied. However, most previous publications focused their studies on PONV during the first 24 h, and less is known about this complication during the ensuing days, its impact on nutritional recovery or its relation to other complications and the course of care. Methods: An observational study involving 806 consecutive patients in a colorectal Enhanced Recovery After Surgery (ERAS) programme was performed. The primary objective was to analyse the incidence of early PONV on the day of surgery and the following 2 postoperative days (late PONV). Secondary objectives included evaluation of the influence of late PONV over the LOS and the nutritional recovery adjusted for confounding factors. Results: PONV tended to increase over time (7% vs 7% and 10%, postop days 0, 1 and 2, respectively; p < 0.05). PONV on day 2 was associated in an adjusted analysis with poor oral intake, delayed solid food tolerance and an average increase in LOS of 2 nights. Risk factors for the presence of PONV on day 2 were the use of opioids on the same day, PONV on the day of the surgery and rectal procedures. Conclusions: PONV continues to be frequent after the first 24 h in colorectal surgery despite high compliance to current anti emetic recommendations. PONV during day 2 negatively affects the nutritional postoperative recovery and independently prolongs the hospital stay. The findings of the current study highlight the adverse effects of opioids and the need of further discussion on how to best audit, prevent and treat late PONV in ERAS colorectal programmes.